Online community business model to enhance the sustainability of family business - Anita Wijayanti (2023)
The COVID-19 pandemic hitting the world has caused many companies to go into liquidation. Family business is one of the companies that are forced to go into liquidation. Family business aims for sustainability, so that it can be a legacy left for the next generation. This is a serious problem for family business. Moreover, family business must face changes in the business environment and technology. Family business also has weaknesses in terms of resources. Family business must find solution to enhancing their sustainability. Several studies state that online business is an alternative model of family business. Therefore, this research is important since it examines an appropriate business model to enhance the sustainability of family business. Some experts state that family business is unique, that family as a strong community. The researcher assumes that the appropriate model for family business is based on the two theories above. In several theories on online business model, there are theoretical concepts of Community-based online business model. Community-based online business model is recommended to enhance the sustainability of family business. The weaknesses in the theory of the community-based online business model are inconsistencies in the analyses of the community in online business model theories due to the lack of a clear definition of community-based online business. The problem statement of this research is (1) What are the attributes of online community business model that may enhance the sustainability of family business? (2) How to develop online community business model that may enhance the sustainability of family business? (3) To what extent does online community business model facilitate the sustainability of family business? This research used a mixed method and aimed to 1) examine the attributes of online community business model that may enhance the sustainability of family business; 2) analyze online community business model that may enhance the sustainability of family business, and 3) analyze the feasibility of online community business model to enhance the sustainability of family business. The results of this study indicate four main attributes of the online community business model, as follows: community, strategic alliance, business platform, and business transformation. There are many activities arising from the implementation of online community business model in family businesses. Therefore, the online community business model is also prepared based on family business’s activities. The overall structured online community business model indicates a conceptual framework and a series of activities in a comprehensively structured online community business. The evaluation was carried out to ensure that the online community business model is feasible to be applied to family business. The evaluation results show that the online community business model is feasible since it has appropriate scientific principles and practices and can enhance the sustainability of family business. The developed model can be used to solve several problems faced by family businesses and provides guidelines for carrying out procedures for changing business direction from traditional to online. This research also provides input to company owners or family business management on how to change their mindset when operating a business in a community model or collaborating with other companies.